THE IDEOLOGIZATION OF CULTURE AS THE BASIS OF ITS DEFORMATION IN TOTALITARIAN SOCIETIES - Serhii Mahera ("Scientific Information Agency "Science-technologies-information" LLC, 2019)
In a strategic dimension, the task of the Soviet government was to reduce the influence of national culture and replace it with ideological postulates, which ensured the consolidation of peoples, but the illusionary consolidation, which was fundamentally false. The blurring of the national foundations of the life of ethnic groups became the basis for the destruction of culture, and then the destruction of man, people, nation. One of the effective tools of such a policy of the Soviet government during the entire period of the existence of a totalitarian state was the deprivation of national cultures and educational institutions of the opportunity to develop on the basis of national-linguistic ground, which is a phenomenological and semantic source for the development of any culture.